Investigating the Antibacterial Ability of Sodium Hypochlorite Solution Activated with PUI and XPF File Against Enterococcus faecalis Using CFU, RT-PCR, and SEM - Radovan Jovanović; Jugoslav Ilić; Ljiljana Šubarić; Zoran Vlahović; Sanja Simić; Zoran Arsić; Milena Radunović; Branka Popović (Bioengineering)
Eradication of microorganisms present in the root canal system during endodontic therapy is one of the critical factors affecting the final outcome of endodontic treatment. However, even adequate technique of the root canal treatment and use of irrigants according to the established protocol does not lead to the complete elimination of microorganisms during endodontic treatment. The presence of Enterococcus (E.) faecalis inside the root canal system may be an important factor contributing to the failure of the treatment. Introducing agitation techniques in irrigation, such as passive ultrasonic irrigation (PUI) and the use of the activating instrument XP-endo Finisher (XPF), contribute to a better debridement and disinfection of the root canal. This study was conducted on 42 root canals experimentally inoculated with E. faecalis and exposed to three irrigation protocols. These have included a standard irrigation protocol using a syringe and needle, passive ultrasonic irrigation, and activation of the irrigant using an XPF instrument. The reduction in microorganisms was evaluated using the quantitative polymerase chain reaction in real-time (RT-PCR) as well as via the method of determining the number of colony forming units on nutrient medium (CFUs). The results of this study showed that the use of supplementary irrigation protocols, PUI, and XPF led to a significant decrease in the number of microorganisms inside the root canal of experimental teeth. These findings indicate a significant positive impact of these procedures on the disinfection of the root canal system.